The handbook of European intellectual property management : developing, managing, and protecting your company's intellectual property - Jolly, Adam (London: Kogan page, 2007)
"Bringing together a wide range of expert contributors, The Handbook of European Intellectual Property Management reveals how IP can contribute to improved competitive performance and financial success. Looking at the commercial implications of the changes that are happening within Europe's framework for innovation, like the arrival of the unitary patent, the book reviews how EU programs such as Horizon 2020, the Innovation Union and the European Research Area are creating growth from IP ventures. Additionally, the contributors discuss the new terms on which leading players in business and research are looking to engage partners in sourcing ideas and fast-tracking innovation.Chapter topics include: designing an IP strategy; capturing and securing IP; capitalizing on new technologies; combining different types of IP; whether to adopt a national, European or global focus; engaging in partnerships and competitions; how to source ideas from the research base; which model to adopt in reaching the market; negotiating IP within contracts; putting a value on IP; raising funds with IP; how to resolve disputes"--
"When managed well, IP can become the most enduring form of competitive advantage, creating streams of revenue well into the future. But for many in Europe, IP can still seem complicated to acquire, expensive to maintain and hard to enforce. Drawing on a wide range of expert contributions, The Handbook of European Intellectual Property Management is a practical and easy-to-follow account of how IP comes into play at various stages of ventures and delivers commercial success and real competitive advantage. Drawing out the commercial implications of the changes that are happening within Europe's framework for innovation, like the arrival of the unitary patent, this Handbook reviews how EU programmes such as Horizon 2020, the Innovation Union and the European Research Area are measuring performance against a target of creating more growth from IP ventures. In parallel, the contributors discuss the new terms on which leading players in business and research are looking to engage partners in sourcing ideas and fast-tracking innovation. Everywhere IP policies are being re-written to encourage open innovation and to source knowledge from wherever it may best be found. For those looking to take an innovation, a design, or a brand into the market, this handbook discusses the options in putting the right idea into the right format, highlighting challenges such as: - how to design an IP strategy - how to capture and secure IP - how to capitalise on new technologies - how to combine different types of IP - whether to adopt a national, European or global focus - how to engage in partnerships and competitions"--
Includes bibliographical references.
Keywords: Intellectual property -- European Union countries; Intellectual property -- European Union countries -- Management; Technological innovations -- European Union countries -- Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / International / General; LAW / Intellectual Property / General